Trastorno del Espectro Autista y desarrollo cognitivo: Propuesta de intervención en niños de 6 a 8 años de la Unidad Educativa Gabriela Mistral. Cantón Pelileo. Periodo 2023-2024. - Amán Villena, Gabriela Alejandra (2024)
The present work of curricular integration with the theme Autism Spectrum Disorder and cognitive development: Proposal of intervention in children from 6 to 8 years old of the Gabriela Mistral Educational Unit. Pelileo Canton. Period 2023-2024, had as general objective to analyze the Autism Spectrum Disorder and cognitive development in children from 6 to 8 years old of the Gabriela Mistral Educational Unit. Pelileo Canton. Period 2023-2024. It was a qualitative, descriptive, non-experimental design study. Observation and interview forms were applied to the sample of 2 teachers. The results found in the pre-interview directed to teachers showed that they know very little about ASD and do not know how to intervene adequately in their students with this disorder; following these results, a workshop was conducted for teachers in order to train and equip them with effective strategies to strengthen cognitive development in children 6 to 8 years old with ASD, this consisted of a guide of methodological strategies, structured by 8 activities. After the implementation of the workshop, the results of the post-test showed a remarkable transformation in the educational dynamics and well-being of the students. Prior to the implementation, there was significant variability in the understanding and management of ASD among teachers, which often resulted in educational strategies that were not always adequate to the specific needs of these students. However, after the implementation of the workshop, teachers demonstrated a greater understanding of the characteristics of ASD, having tools for comprehensive inclusive teaching in the classroom. It is concluded that, in the pre-test, that the activity guide trained teachers in specific strategies for working with students with ASD, also strengthened the educational community by fostering a more inclusive, understanding and cooperative institutional environment.